The standard international prognostic index for predicting the risk of CNS involvement in DLBCL without specific prophylaxis - Tomita, Naoto; Yokoyama, Masahiro; Yamamoto, Wataru; Watanabe, Reina; Shimazu, Yutaka; Masaki, Yasufumi; Tsunoda, Saburo; Hashimoto, Chizuko; Murayama, Kayoko; Yano, Takahiro; Okamoto, Rumiko; Kikuchi, Ako; et al. (Leukemia & lymphoma, 2018)
Central nervous system (CNS) involvement is a serious complication in patients with diffuse large B-cell lymphoma (DLBCL) and evaluating CNS risk is an important issue. Using the standard international prognostic index (IPI) and CNS-IPI, a recently proposed model including IPI risk factors and adrenal/kidney involvement, we assessed CNS risk in 1220 untreated DLBCL patients who received R-CHOP without prophylaxis. According to the standard IPI, the cumulative incidences of CNS involvement at 2 years were 1.3, 4.6, 8.8, and 12.7% in the low-, low-intermediate-, high-intermediate-, and high-risk groups, respectively (p <.001). This result is comparable with that of the CNS-IPI. Patients with breast involvement tended to have lower risk according to the standard IPI but showed frequent CNS involvement, similar to patients with testis involvement. The standard IPI is also a useful predictor of CNS involvement. Patients with breast/testis involvement would be candidates for prophylaxis regardless of the standard IPI risk.